2021
DOI: 10.1002/elps.202000233
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of microorganisms with nonlinear electrokinetic microsystems

Abstract: Nonlinear electrokinetics (EK), specifically electrophoresis of the second kind, dielectrophoresis (DEP) and electrorotation (EROT), have gained significant interest recently for their flexibility and labeless discriminant manner of operation. The current applications of these technologies are a clear advancement from what they were when first discovered, but also still show strong signs of future growth. The present review article presents a discussion of the current uses of microscale nonlinear EK technologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 81 publications
(195 reference statements)
0
12
0
Order By: Relevance
“…Polaczyk et al [4] recently published an excellent study on the calculation of zeta potential of microorganisms and Antunez-Vela et al [5], reported the first experimental assessment of the nonlinear electrophoretic mobility of bacterial and yeast cells. Exploiting differences in electrical properties offers an alternative for the rapid identification or separation of microorganisms [1,3].…”
Section: Abbreviationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Polaczyk et al [4] recently published an excellent study on the calculation of zeta potential of microorganisms and Antunez-Vela et al [5], reported the first experimental assessment of the nonlinear electrophoretic mobility of bacterial and yeast cells. Exploiting differences in electrical properties offers an alternative for the rapid identification or separation of microorganisms [1,3].…”
Section: Abbreviationsmentioning
confidence: 99%
“…Electromigration techniques also face challenges for the identification of highly similar microorganisms with comparable electromigration behavior. In these cases, nonlinear electrode-based or insulator-based EK systems can provide an alternative, as they have proved to have highly discriminatory capabilities for the analysis of a wide range of particles, from macromolecules to parasites [1,5,[13][14][15][16][17].…”
Section: Abbreviationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Insulator-based dielectrophoresis (iDEP) is an emerging technique that has been increasingly used in the past two decades for microfluidic applications. It utilizes single or multiple insulating structures to create electric field gradients for various manipulations of particles and cells in Newtonian fluids [13][14][15][16]. However, many biological (e.g., blood and saliva) and chemical (e.g., colloidal and polymer solutions) fluids exhibit non-Newtonian characteristics [17,18].…”
Section: Introductionmentioning
confidence: 99%